2019
DOI: 10.1111/tbed.13223
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma bovis and viral agents associated with the development of bovine respiratory disease in adult dairy cows

Abstract: The etiology and pathologic findings of bovine respiratory disease (BRD) in adult dairy cows (n = 35) from a commercial dairy herd in Southern Brazil were investigated. Pulmonary samples were examined for histopathologic patterns and specific features within these patterns, while immunohistochemical (IHC) assays were designed to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…We found that M. bovis infection was associated with the detection of higher numbers of viruses ( p = .002). Further, bronchiolitis obliterans, which is regarded as a chronic lesion, was associated with M. bovis infection, consistent with results of a recent study using immunohistochemistry (IHC) to analyse association of histological features with infectious agents in dairy cows (Oliveira et al, ). It is possible that chronic M. bovis infection can compromise host immunity and lead to infection with multiple viruses, or alternatively, multiple viral infections could predispose cattle to M. bovis infection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that M. bovis infection was associated with the detection of higher numbers of viruses ( p = .002). Further, bronchiolitis obliterans, which is regarded as a chronic lesion, was associated with M. bovis infection, consistent with results of a recent study using immunohistochemistry (IHC) to analyse association of histological features with infectious agents in dairy cows (Oliveira et al, ). It is possible that chronic M. bovis infection can compromise host immunity and lead to infection with multiple viruses, or alternatively, multiple viral infections could predispose cattle to M. bovis infection.…”
Section: Discussionsupporting
confidence: 87%
“…Advances in BRD epidemiology, pathogen genomics and proteomics, characterization of the respiratory tract microbiome and the development of experimental challenge models (Fulton, ) have led to an evolution of our understanding of the relationship of pneumonic lesions with infectious pathogens originally reported in the 1970s (Jensen et al, , ). Most recently, application of advanced technologies for virus identification has resulted in further insight into the relationships between well‐recognized pathogens and BRD (Booker et al, ; Mehinagic et al, ; Oliveira et al, ). Previously, we detected 21 viruses in bovine nasal swabs and tracheal washes from western Canadian beef cattle, among which IDV, BRBV, BRSV and BCV were significantly associated with BRD (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…BPI-3, BoHV-1, and M. haemolytica were not detected in BALF samples these calves evaluated. In Brazilian cattle herds, BPI-3 was detected in few studies, isolated in a single animal in south of the country [38] and another study using immunohistochemical it was detected in four animals [39], but in the most BRD studies was not found [3,18,22,36]. Possibly, BPI-3 circulates with low frequency in Brazilian cattle herds.…”
Section: Discussionmentioning
confidence: 97%
“…Diagnostic techniques used in previous investigations of mixed infections in BRD cases in Brazil usually include pathological examination, serology, bacterial cultures and/or virus isolation [21,23,38,40]. However, these techniques may be appropriate for one agent but not for the other due to different sensitivity values [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation